Chronological analysis of canine parvovirus type 2 isolates in Japan - Ohshima, T.(Kyoritsu Seiyaku Corp., Tsukuba, Ibaraki (Japan). Tsukuba Central Labs.); Hisaka, M; Kawakami, K; Kishi, M; Tohya, Y; Mochizuki, M (Journal of Veterinary Medical Science, 2008)
Fifty-five canine parvovirus type 2 (CPV) samples, 12 fecal specimens and 43 cell culture isolates, were examined for their genetic characteristics of VP2 gene. They were collected from the diseased dogs at various districts of Japan during 27 years from 1980 to 2006. A fragment of VP2 gene was analyzed by restriction fragment length polymorphism assay and DNA sequencing. The original antigenic type 2 of CPV (CPV-2) was no longer found in the samples since 1984, and two antigenic variants CPV-2a and CPV-2b replaced CPV-2 as predominant types for about 5 years from 1982. A new genetic variant of prototype CPV-2a with non-synonymous substitution at the VP2 amino acid residue 297 from Ser to Ala was first detected in 1987. New CPV-2b with the same amino acid substitution at position 297 as new CPV-2a was also detected from the samples collected in 1997. Since then new CPV-2b has been the predominant CPV over the field of Japan. Several additional amino acid substitutions were detected in the VP2 gene of some recent CPV strains. Neither CPV-2c(a), CPV-2c(b), nor 'Glu-426' of the antigenic variants previously found outside the country was detected in any samples tested. Reactivity of new CPV-2a and 2b variants against antibodies produced by the current vaccine products was determined by a cross hemagglutination-inhibition test. The recent field CPV isolates reacted more efficiently to the antibodies produced in dogs vaccinated with the new CPV-2b vaccine strain than the conventional CPV-2 vaccine strain.